Solitary man [videorecording (DVD)] - Penn, Michael (2010)
Ben Kalmen, a fifty-something New Yorker, discovers that he is not the man he wanted to be. Through many business and romantic indiscretions he has lost his once successful car dealership. Now he must make the decision to face the challenges of his not so youthful life.